2020
DOI: 10.1021/acs.est.9b07473
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hydrolysis of p-Nitrophenyl Phosphate by Iron (Hydr)oxide Nanoparticles: Roles of Exposed Facets

Abstract: Iron (hydr)­oxide nanoparticles are one of the most abundant classes of naturally occurring nanoparticles and are widely used engineered nanomaterials. In the environment these nanoparticles may significantly affect contaminant fate. Using two goethite materials with different contents of exposed {021} facet and two hematite materials with predominantly exposed {001} and {100} facets, respectively, we show that exposed facets, one of the most intrinsic properties of nanocrystals, significantly affect the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 67 publications
6
23
1
Order By: Relevance
“…76 The higher density of singly coordinated hydroxyl groups on the {100} surface of hematite was also shown to be responsible for the greater sorption capacity (per surface area) of humic substances compared with the {001} facet, 235 with analogous conclusions for enhanced sorption and subsequent hydrolysis of 4-nitrophenyl phosphate on the {100} vs. {001} facet of nanohematite. 238 In addition to relative differences in sorption capacities, recent research has demonstrated that different facets of nanoscale hematite also promote different complexation geometries for both inorganic and organic contaminants. For example, Huang et al showed that chromate bound via a monodentate, mononuclear complex on the {001} facet, but on the {110} facet bound as a bidentate, binuclear complex, and was removed with much greater efficiency.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…76 The higher density of singly coordinated hydroxyl groups on the {100} surface of hematite was also shown to be responsible for the greater sorption capacity (per surface area) of humic substances compared with the {001} facet, 235 with analogous conclusions for enhanced sorption and subsequent hydrolysis of 4-nitrophenyl phosphate on the {100} vs. {001} facet of nanohematite. 238 In addition to relative differences in sorption capacities, recent research has demonstrated that different facets of nanoscale hematite also promote different complexation geometries for both inorganic and organic contaminants. For example, Huang et al showed that chromate bound via a monodentate, mononuclear complex on the {001} facet, but on the {110} facet bound as a bidentate, binuclear complex, and was removed with much greater efficiency.…”
Section: Applicationsmentioning
confidence: 99%
“…For example, Catalano et al have reported the preference of arsenate (As­(VI)) and selenite (Se­(IV)) to bind to singly and triply coordinated oxygen functional groups because of favorable sterics, kinetics, and acidities. , Noerpel et al used resonant anomalous X-ray reflectivity (RAXR) to determine the surface coverages of Pb 2+ sorbed on various hematite facets and similarly showed that the {012} and {110} facets (with higher densities of singly and triply coordinated hydroxyl groups than {001}) had a higher surface coverage of Pb 2+ per surface area . The higher density of singly coordinated hydroxyl groups on the {100} surface of hematite was also shown to be responsible for the greater sorption capacity (per surface area) of humic substances compared with the {001} facet, with analogous conclusions for enhanced sorption and subsequent hydrolysis of 4-nitrophenyl phosphate on the {100} vs. {001} facet of nanohematite …”
Section: Applicationsmentioning
confidence: 99%
“…The results of previous studies showed that the exposed facets affect the adsorption of proteins and heavy metals, the decomposition of organic pollutants on metal oxides, , and the mobility and fate of OM components. , The combination between Fe oxides and OM is mainly driven by surface complexation between carboxyl groups in OM and surface Fe atoms. During the adsorption process, OM molecules with a high oxidation state and high aromaticity preferentially form ligand-exchange complexes with hydroxyl functional groups on the hematite surface, and OM components with low molecular weight exhibit a strong facet-dependent selective fractionation .…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous studies showed that the exposed facets affect the adsorption of proteins 27 and heavy metals, 28−30 the decomposition of organic pollutants on metal oxides, 31,32 and the mobility and fate of OM components. 22,23 The combination between Fe oxides and OM is mainly driven by surface complexation between carboxyl groups in OM and surface Fe atoms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There has been extensive research on crystal facet engineering and the role of special facets in affecting the fate of environmental contaminants, like TiO 2 and FeWO 4 materials. It was reported that anatase (TiO 2 ) crystals with highly exposed active {001} facets had the enhanced ability of photocatalytic performance .…”
Section: Introductionmentioning
confidence: 99%